2003
DOI: 10.1088/0031-9155/48/3/306
|View full text |Cite
|
Sign up to set email alerts
|

Poly(vinyl alcohol) gels for use as tissue phantoms in photoacoustic mammography

Abstract: Materials for solid photoacoustic breast phantoms, based on poly(vinyl alcohol) hydrogels, are presented. Phantoms intended for use in photoacoustics must possess both optical and acoustic properties of tissue. To realize the optical properties of tissue, one approach was to optimize the number of freezing and thawing cycles of aqueous poly(vinyl alcohol) solutions, a procedure which increases the turbidity of the gel while rigidifying it. The second approach concentrated on forming a clear matrix of the rigid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
140
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(145 citation statements)
references
References 25 publications
3
140
1
1
Order By: Relevance
“…The static layer is made of a poly(vinyl alcohol) (PVA) gel with polystyrene particles. In the past, PVA has been used to produce elastic [10] or viscoelastic [11] gels as optical tissue phantoms. The advantage of PVA is its solubility in water, so we can make phantoms of known scattering and absorption properties by adding polystyrene spheres and water-soluble dyes before gelation.…”
Section: Methodsmentioning
confidence: 99%
“…The static layer is made of a poly(vinyl alcohol) (PVA) gel with polystyrene particles. In the past, PVA has been used to produce elastic [10] or viscoelastic [11] gels as optical tissue phantoms. The advantage of PVA is its solubility in water, so we can make phantoms of known scattering and absorption properties by adding polystyrene spheres and water-soluble dyes before gelation.…”
Section: Methodsmentioning
confidence: 99%
“…Polyvinyl alcohol (PVA) was chosen since PVA phantoms are resilient and can be stored for a long time (Hassan and Peppas 2000). Further, the ultrasonic (Surry et al 2004), optical (Kharine et al 2003), mechanical (Fromageau et al 2003) and thermal (Sundararajan 1999) properties of polyvinyl alcohol are well characterized and the material is suitable for multi-modal imaging studies. Generally, the composite vascular phantoms in our studies contained an inclusion embedded into an otherwise homogeneous vessel wall.…”
Section: A Arterial Vessel Samplesmentioning
confidence: 99%
“…[26][27][28][29] TMM phantoms bridge the gap in translational research without the need of direct experimentation on humans or animals. The phantoms designed with TMMS are essential for assessing different technologies, and for training and research.…”
Section: Introductionmentioning
confidence: 99%
“…Various kinds of TMMs have already been used in ultrasound research, such as gelatine, agar, silicone, and polyacrylamide (PAA) gel. [26][27][28][29] The key parameters in material characterization for ultrasound imaging include the acoustic velocity, the acoustic impedance, and the acoustical attenuation, while Young's modulus is an important parameter for elastography phantoms. Madsen et al 30 have demonstrated the use of TM phantoms for standardization of both ultrasound imaging of the prostate 26 and for elastographic imaging 18, 31 using agar and gelatine materials.…”
Section: Introductionmentioning
confidence: 99%